Scattering of the Fundamental Anti-symmetric Lamb Wave by a Mid-plane Edge Delamination in a Fiber-composite Laminate. (2017) - Chiu, W.K.; Rose, L.R.F.; Nadarajah, N.
Abstract: This paper investigates the scattering of the fundamental anti-symmetric Lamb wave mode by a delamination along the edge of a quasi-isotropic fiber-composite laminate. Delaminations pose a serious threat to the structural integrity of composite laminates as they often show no visible signs of damage on the surface. Due to the anisotropic nature of composites, analytical solutions are often complicated to derive for such problems. This investigation uses 3D Finite Element (FE) analysis and experimental tools to characterize the scatter by a mid-plane delamination in composites. A 5.5 cycle Hann windowed wave train was used as the input signal for both FE and experiments. A 2D Fast Fourier Transform was used to identify the mode and amplitude of the scattered field along various scattered directions. The experimental wave field image was captured using a 3D Laser Vibrometer. The results indicate that the scatter pattern is much more complex than previously obtained results for an isotropic plate. Even for the simple case of mid-plane delamination, the fiber steering effects in the outermost plies have a significant effect on the scattering pattern, relative to the isotropic case where the dominant part of the scattered field is an edge-guided wave. Computational and experimental results are presented for the scattering pattern and scattering amplitude as a function of damage size relative to wavelength. The implications of these results for the optimal placement of actuators and sensors for Structural Health Monitoring (SHM) purposes, and for devising effective approaches for the inverse problem of damage detection and sizing, are briefly discussed.